The effects of interface and matrix reinforcements on fracture toughness of E-Glass/epoxy laminate - Goksel Saracoglu; Ahmet Yapici (Materials Research Express, 2020)
In this study, the effects of low amount (0.1 wt%) multi-walled carbon nanotube (MWCNTs) distributed homogenously in epoxy via cationic surfactant (cetyl pyridiniumchloride-CPC), polyacrylonitrile nanofiber (in the range of 240–570 nm diameter) mats between each lamina, main fiber-matrix interface improvement using γ -Glycidoxypropyltrimethoxysilane and intermediate combinations were investigated on the fracture toughness of E-Glass/epoxy laminate. Considering the data obtained from three-point bending test samples with a single edge crack, it was found that the ultimate bending strength, modulus and fracture toughness of the silane-treated samples increased by 25.6%, 4.9 and 16.6% respectively, with respect to the reference sample. When MWCNTs was added to the silane treated sample, it was observed that it did not enhance the fracture toughness and decreased the strength and modulus slightly (1%) with the effect of CPC. The effect of 128 μ m thick nanofiber mats on the silane-treated sample did not occur as expected and was found to cause delamination by working as a separate layer between the laminae.